Priorities for Future Innovation, Research, and Advocacy in Dental Restorative Materials. (November 2013) - Watson, T.; Fox, C.H.; Rekow, E.D.
Innovations in materials science, both within and outside of dentistry, open opportunities for the development of exciting direct restorative materials. From rich dialog among experts from dental and non-dental academic institutions and industry, as well as those from policy, research funding, and professional organizations, we learned that capitalizing on these opportunities is multifactorial and far from straightforward. Beginning from the point when a restoration is needed, what materials, delivery systems, and skills are needed to best serve the most people throughout the world's widely varied economic and infrastructure systems? New research is a critical element in progress. Effective advocacy can influence funding and drives change in practice and policy. Here we articulate both research and advocacy priorities, with the intention of focusing the energy and expertise of our best scientists on making a difference, bringing new innovations to improve oral health.